Reinforcement losses in soil stabilisation due to decomposing roots of Chrysopogon zizanioides and Chrysopogon nemoralis - Phan, Trung Nghia; Leung, Anthony Kwan; Kamchoom, Viroon; Likitlersuang, Suched (My University, 2023)
Quantifying evolutions of the biomechanical properties and mechanical root reinforcement to soil with the duration of root decomposition is important to land management strategy and to soil stabilisation purposes. However, the variations of these properties of the roots of herbaceous species, especially following herbicide application in agriculture practices, have rarely been studied. This study aims to measure the effects of root decomposition due to herbicide on the root biomechanical properties and root reinforcement provided by two contrasting vetiver species (Chrysopogon nemoralis and Chrysopogon zizanioides). We applied herbicide (i.e., propanil) to four treatments of each species, considering four different durations of decomposition (7-, 28-, 56- and 112-days since herbicide application). The biomechanical properties were measured by uniaxial tensile tests, whereas the root reinforcement to poorly graded sand (SP) was quantified by direct shear tests. Root decomposition significantly reduced mean root tensile strength, secant modulus and breakage strain of C. nemoralis and C. zizaniodes roots after 112 days since the herbicide application. Significant negative power correlations between root diameter and root strength (or root secant modulus) (R2 = 0.39–0.86; p-value < 0.05) were identified. Root decomposition did not change the shape of these correlations, but they shifted downwards as roots decomposed. The root reinforcement also declined with the decomposition duration, in terms of root cohesion and maximum dilatancy within the study period. C. nemoralis displayed greater and quicker loss of both the root biomechanical properties and root reinforcement to soil than C. zizanioides.
Keywords: root biomechanical properties; root decomposition; root reinforcement; vegetated soil